Effect of Hypericum perforatum Extract in an Experimental Model of Binge Eating in Female Rats. (10th September 2012) - Micioni Di Bonaventura, Maria Vittoria; Vitale, Giovanni; Massi, Maurizio; Cifani, Carlo
Abstract : Purpose . The present study evaluated the effect of Hypericum perforatum dry extract in an experimental model of binge eating (BE). Methods . BE for highly palatable food (HPF) was evoked in female rats by three 8-day cycles of food restriction/re-feeding and acute stress on the test day (day 25). Stress was induced by preventing access to HPF for 15 min, while rats were able to see and smell it. Hypericum perforatum dry extract was given by gavage. Results . Only rats exposed to both food restrictions and stress exhibited BE. The doses of 250 and 500 mg/kg of Hypericum perforatum extract significantly reduced the BE episode, while 125 mg/kg was ineffective. The same doses did not affect HPF intake in the absence of BE. The dose of 250 mg/kg did not significantly modify stress-induced increase in serum corticosterone levels, suggesting that the effect on BE is not due to suppression of the stress response The combined administration of 125 mg/kg of Hypericum perforatum together with Salidroside, active principle of Rhodiola rosea, produced a synergic effect on BE. Conclusions . The present results indicate for the first time that Hypericum perforatum extracts may have therapeutic properties in bingeing-related eating disorders.